Impaired hemodynamic activity in the right dorsolateral prefrontal cortex is associated with impairment of placebo analgesia and clinical symptoms in postherpetic neuralgia. (June 2020) - Hibi, Daisuke; Takamoto, Kouichi; Iwama, Yudai; Ebina, Shohei; Nishimaru, Hiroshi; Matsumoto, Jumpei; Takamura, Yusaku; Yamazaki, Mitsuaki; Nishijo, Hisao
Highlights: Patients with chronic pain due to postherpetic neuralgia (PHN) were used. Hemodynamic activity in the dorsolateral prefrontal cortex (dlPFC) was analyzed. PHN showed less placebo effects and smaller hemodynamic responses in the right dlPFC. PHN symptoms were associated with smaller placebo effects and right dlPFC responses. Deficits in placebo effects due to dlPFC disturbance are involved in chronic pain. Abstract: The dorsolateral prefrontal cortex (dlPFC) is functionally linked to the descending pain modulation system and has been implicated in top down pain inhibition, including placebo analgesia. Therefore, functions of the dlPFC may be impaired in patients with chronic pain. Postherpetic neuralgia (PHN) is one of several syndromes with chronic neuropathic pain. In the present study, we investigated possible dysfunction of the dlPFC in chronic pain using patients with PHN. In a conditioning phase, heathy controls (n = 15) and patients with PHN (n = 7) were exposed to low (LF) and high (HF) frequency tones associated with noxious stimuli: weak (WS) and strong (SS) electrical stimulation, respectively. After the conditioning, cerebral hemodynamic activity was recorded from the bilateral dlPFC while the subjects were subjected to the cue tone-noxious electrical stimulation paradigm, in which incorrectly cued noxious stimuli were sometimes delivered to induce placebo and nocebo effects. The results indicated that hemodynamic responses to the LF tone in the right dlPFC was significantly lower in patients with PHN compared to the healthy controls. Furthermore, the same hemodynamic responses in the right dlPFC were correlated with placebo effects. In addition, clinical symptoms of PHN were negatively correlated to cerebral hemodynamic responses in the right dlPFC and magnitudes of the placebo effects. The results suggest that the right dlPFC, which is closely associated with the descending pain modulation system, is disturbed in PHN.